Optimization of a Low-Cost Force Sensor for Spinal Orthosis Applications - Evans, Katherine R.; Lou, Edmond; Faulkner, Gary (IEEE transactions on instrumentation and measurement, 2013)
Force sensors have been reported to be reliable for monitoring spinal orthosis compliance in the treatment of scoliosis. However, the current force sensor used for these compliance monitors has certain limitations and drawbacks. A lower cost force sensor with a 55% larger operating force range was chosen for this application, with modifications required to increase its contact surface, improve comfort, and reduce the manufacturing time. Different designs have been considered and described in this paper. A final prototype using a rubberlike material housing with a stiff nub over the sensing area of the original sensor produced a linear, highly sensitive, large surface area, reliable, and robust sensor. It has a sensitivity of 315 mV/N, accuracy 1.9%, repeatability 0.6%, linearity 0.7%, hysteresis 0.8%, dead band 0.0%, point drift 0.5%, temperature drift 2.2% for the temperature range 25 °C- 35 °C, and reproducibility 1.3%. These properties are adequate for measuring forces in a spinal orthosis. The total cost of the sensor with housing is 46 when ordered in quantities of 1000, which reduces the price of the existing sensor by 34%. The manufacturing time of the new sensor was reduced and a preliminary subject trial demonstrated that the new sensor did not have significant temperature effect. This will make force systems more affordable and adaptable for the effective treatment of scoliosis.